MEMAHAMI ISLAM LOKAL MELALUI KITAB SERIBU MASAIL: STUDI KOMPARASI TEKS ARAB-MELAYU - Lutfiyah Alindah (Universitas Negeri Surabaya, 2015)
The spread and development of Islam in the Indonesia not only brought Islam together, but also brought Islamic culture in the form of literature. The development in teaching Islamiccultural tradition is important in the process of Islamization. Many books were translated, composed or adapted to many languages in the archipelago. The books are compiled in what is known as sastra kitab (literature of Islamic theology). Its two versions, the Masail Sayyidi 'Abdullah bin Salam lin Nabi in the Arabic version or Seribu Masail in Malay version, are still preserved. Both of these texts are part of the process of translation from Arabic texts into Malay text which have variations either in structure linguistic or meaning.This paper examines the variations occurring in process of translation between Arabic text and Malay text, and how the variations are manifested in these two texts. This research is important because it looks at Sirah nabawiyah (history of the prophet) that documents both written and verbal teachings of Islam. In addition, this study contains the theological values and dialogue between Muslims and non-Muslims. By using George Steiners theory, this study tries to examine the difficulties and the paradoxes created by translation from one language to another.This study demonstrates that the final translation between MasÄil Sayyidi ˜AbdullÄh Bin SalÄm li-NabÄ« text and Seribu Masa'il have variations both in the structure of linguistics and meanings.